Novel Fluorite‐Structured Materials for Solid‐State Refrigeration. Issue 23 (20th April 2022) - Ali, Faizan; Abbas, Akmal; Wu, Guoyi; Daaim, Muhammad; Akhtar, Awais; Kim, Ki‐Hyun; Yang, Boxiong
Abstract: Refrigeration based on the electrocaloric effect can offer many advantages over conventional cooling technologies in terms of efficiency, size, weight, and power source. The discovery of ferroelectric and antiferroelectric properties in fluorite‐based materials in 2011 has led to diverse applications related to memory (e.g., ferroelectric tunnel junctions, nonvolatile memory, and field‐effect transistors) and energy fields (e.g., energy storage and harvesting, electrocaloric refrigeration, and infrared detection). Fluorite‐based materials exhibit several properties not shared by most conventional materials (such as in terms of compatibility with complementary metal‐oxide semiconductors and 3D nanostructures, deposition thickness at the nanometer scale, and simple composition). Here, the electrocaloric refrigeration properties of fluorite‐based ferroelectric/antiferroelectric materials are reviewed by focusing on the advantages of ZrO2 ‐ and HfO2 ‐based materials (e.g., relative to conventional perovskite‐ and polymer‐based counterparts). Finally, the recent progress made in this research field are also discussed along with its future perspectives. Abstract : Refrigeration based on the electrocaloric effect can offer many advantages over conventional cooling technologies (e.g., in terms of efficiency, size, weight, and power source). Fluorite‐based materials exhibit several properties not shared by most traditional materials, such as compatibility with complementary metal‐oxide semiconductors and 3D nanostructures, low deposition thickness, and simple composition. This review sums up the electrocaloric refrigeration properties of fluorite‐based ferroelectric/antiferroelectric materials.